Study on the time-varying fatigue reliability of the invert structure of subway tunnel under the action of train loads - Chen, Zhaofeng; Xu, Linrong; Huang, Changxi; Wu, Lei; Shang, Yonghui (Frontiers in Earth Science, 2023)
Introduction: The present study examines the fatigue reliability of subway tunnel invert structures subjected to train-induced loads, a critical factor in ensuring the safety and longevity of these vital infrastructures. Methods: By integrating higher-order moment theory, fatigue equations, and cumulative damage theory, this research analyzes the impact of train loads on invert structures, taking into account factors such as tension stress, compression stress, train axle weight, speed, and lining thickness. Results: The findings indicate that the reinforcement of the invert structure is required under tension stress, while it is not necessary for compression stress. Notably, the train’s axle weight and speed exert a significant influence on the fatigue reliability index, with speed displaying a marginally greater effect than axle weight. Conversely, the lining thickness demonstrates a negligible impact on the reliability index. As time progresses, the fatigue reliability index diminishes, resulting in an elevated probability of failure. Discussion: In light of these findings, it is imperative to conduct regular inspections and maintain the tensile state of the invert structure, which warrants the most attention. To safeguard the safety and longevity of subway tunnel invert structures, it is essential to concentrate on the aspects related to tensile stress and closely monitor train loads, specifically axle weight and speed.